Аналіз патохімічних змін в оці при віковій катаракті методом газорідинної хроматографії - Яценко, О.В.; Брюзгіна, Т.С.; Вретік, Г.М. (Видавничий дім "Академперіодика" НАН України, 2007)
The results of the gas chromatography test of the fat acid spectrum of lipids of blood erythrocytes, lens, and eliminate from the eyes of patients with senile cataract are given. The conducted investigations allowed us to recommend eliminate as a new noninvasive material under clinical conditions for the estimation of lipid metabolism breaks in eyes.